Wear of resin denture teeth in partial removable dental prostheses. Issue 1 (January 2020) - Stober, Thomas; Bermejo, Justo Lorenzo; Rues, Stefan; Rammelsberg, Peter
Abstract: Purpose: To investigate occlusal wear of resin denture teeth in partial removable dental prostheses worn by partially edentulous patients. Methods: Thirty patients with partial removable dental prostheses were included in the study. Thirty-two patients with complete dentures served as a reference group. Occlusal wear after two years was evaluated indirectly using gypsum casts and a three-dimensional laser-scanner device. Overall wear of complete occlusal surfaces and maximum wear of occlusal contact areas were measured. Patient and prosthesis data were analyzed using univariate and multiple linear mixed models. Results: Overall wear of denture teeth in partial removable dental prostheses was 91 (SD 85) μm, and maximum wear of occlusal contact areas was 329 (SD 204) μm (means and standard deviations). Average and maximum wear values for teeth in complete dentures were both lower than those for teeth in partial removable dental prostheses. However, differences between wear of different types of denture did not reach statistical significance after adjustment for gender, type of tooth, dental status of the opposing jaw, and antagonist material. Statistical analysis revealed that wear was greater for denture teeth occluding with ceramic crowns and/or fixed partial dentures as antagonists. Conclusions: Resin denture teeth in partial removable and complete dental prostheses are subjected to clinically important occlusal wear that might destabilize occlusion and cause further problems. Patient-related factors and dental status affect wear behavior and should be taken into consideration when treating patients with removable dentures.